Novel Variants in LRRK2 and GBA Identified in Latino Parkinson Disease Cohort Enriched for Caribbean Origin - Nuytemans, Karen; Rajabli, Farid; Bussies, Parker L.; Celis, Katrina; Scott, William K.; Singer, Carlos; Luca, Corneliu C.; Vinuela, Angel; Pericak-Vance, Margaret A.; Vance, Jeff M. (Frontiers in Neurology, 2020)
Background: The Latino population is greatly understudied in biomedical research, including genetics. Very little information is available on presence of known variants originally identified in non-Hispanic white patients or novel variants in the Latino population. The Latino population is admixed, with contributions of European, African, and Amerindian ancestries. Therefore, the ancestry surrounding a gene (local ancestry, LA) can be any of the three contributing ancestries and thus can determine the presence or risk effect of variants detected. Methods: We sequenced the major exons and exons of reported Latino-specific variants in GBA and LRRK2 and performed genome-wide genotyping for LA assessments in 79 Latino Parkinson disease (PD) patients, of which 80% identified as Caribbean Latino. Results: We observed five carriers of LRRK2 p.G2019S, one GBA p.T408M, and three GBA p.N409S on European as well as three GBA p.L13R on African LA backgrounds. Previous Latino variant GBA p.K237E was not observed in this dataset. A novel highly conserved and predicted damaging variant LRRK2 p.D734N was identified in two unrelated individuals with African LA. Additionally, we identified rare, functional variants LRRK2 p.P1480L and GBA p.S310G in one individual each heterozygous for European/Amerindian LA. Discussion: Additional functional analysis will be needed to determine the pathogenicity of the novel variants in PD. However, the identification of novel disease variants in the Latino cohort potentially contributing to PD supports to importance of inclusion of Latinos in genetics research to provide insight in PD genetics in Latinos specifically as well as other populations with the same ancestral contributions.